Description of clinical factors for suicide attempts in a tertiary care hospital of northern part of India - Sharma, Ravi C.; Sharma, Dinesh D.; Gupta, Vikesh; Gupta, Rahul; Kumar, Vineet; Verma, Kushel (International Journal of Research in Medical Sciences, 2018)
Background: Suicide is the result of an act deliberately initiated and performed by a person in the full knowledge or expectation of its fatal outcome. Suicide attempts are a significant public health problem. The present study aimed to explore the variousclinical characteristics of suicideattempters in a tertiary care hospital of Shimla, Himachal Pradesh, a northern state of India. Methods: We conducted a descriptive study among patients with attempted suicide to the department of Psychiatry, Indira Gandhi Medical College (IGMC) Shimla. A structured, self-designed interview schedule and short-form revised Eyseneck personality questionnaire-Hindi (EPQRS-H) was used for data collection. Data was analyzed using Epi info software v 7.2.0. Results: There were total 77 participants in the study out of which 44 (57.1%) were females. Mean age (Standard deviation) of participants was 30.8 years (9.9 years). Relationship problems were the most common (48.1%) recent life event followed by health events (28.6%). Depression was found to be the most common diagnosis (62.3%). Pesticide consumption was the method of attempting suicide in 72.7% of females compared to 66.7% of males. Conclusions: Recent major life events especially relationship problems may lead to majority of suicide attempts. There is urgent need to focus on patients suffering from depression by health personnel as well as family members. The sale of the pesticides should be regulated to keep in check the misuse of the same.